Exome Sequencing and Linkage Analysis Identified Tenascin-C (TNC) as a Novel Causative Gene in Nonsyndromic Hearing Loss - Zhao, Yali; Zhao, Feifan; Zong, Liang; Zhang, Peng; Guan, Liping; Zhang, Jianguo; Wang, Dayong; Wang, Jing; Chai, Wei; Lan, Lan; Li, Qian; Han, Bing; et al. (PloS one, 2013)
In this study, a five-generation Chinese family (family F013) with progressive autosomal dominant hearing loss was mapped to a critical region spanning 28.54 Mb on chromosome 9q31.3-q34.3 by linkage analysis, which was a novel DFNA locus, assigned as DFNA56. In this interval, there were 398 annotated genes. Then, whole exome sequencing was applied in three patients and one normal individual from this family. Six single nucleotide variants and two indels were found co-segregated with the phenotypes. Then using mass spectrum (Sequenom, Inc.) to rank the eight sites, we found only the TNC gene be co-segregated with hearing loss in 53 subjects of F013. And this missense mutation (c.5317G>A, p.V1773M ) of TNC located exactly in the critical linked interval. Further screening to the coding region of this gene in 587 subjects with nonsyndromic hearing loss (NSHL) found a second missense mutation, c.5368A>T (p. T1796S), co-segregating with phenotype in the other family. These two mutations located in the conserved region of TNC and were absent in the 387 normal hearing individuals of matched geographical ancestry. Functional effects of the two mutations were predicted using SIFT and both mutations were deleterious. All these results supported that TNC may be the causal gene for the hearing loss inherited in these families. TNC encodes tenascin-C, a member of the extracellular matrix (ECM), is present in the basilar membrane (BM), and the osseous spiral lamina of the cochlea. It plays an important role in cochlear development. The up-regulated expression of TNC gene in tissue repair and neural regeneration was seen in human and zebrafish, and in sensory receptor recovery in the vestibular organ after ototoxic injury in birds. Then the absence of normal tenascin-C was supposed to cause irreversible injuries in cochlea and caused hearing loss.